CCK-4: Psychophysiological conditioning elicits features of spontaneous panic attacks - Hinkelmann, Kim; Yassouridis, Alexander; Mass, Reinhard; Tenge, Henrike; Kellner, Michael; Jahn, Holger; Wiedemann, Klaus; Wolf, Karsten (Journal of psychiatric research, 2010)
Cholecystokinin-tetrapeptide (CCK-4) is an established model to generate subjective panic anxiety. CCK-4 injection also results in consistent and dose-dependent rise of stress hormones. Effects other than upon subjective panic and stress hormone activity have barely been examined. The purpose of the study was to investigate CCK-4 effects on emotional facial expression and especially on fear relevant facial muscles establishing therewith a more objective method to measure subjective panic anxiety. 20 healthy male subjects were randomly and double-blindedly assigned in two groups (dose groups), each of which was investigated three times once with placebo and twice with 25 μg or 50 μg CCK-4 respectively. Subjects of each group were randomly assigned in two different balanced orders of investigations: CCK-CCK-Placebo vs. Placebo-CCK-CCK. Facial muscle and hypothalamo-pituitary-adrenocortical (HPA)-axis activity were recorded. CCK-4 led dose-dependently to an increase of panic anxiety, an activation of fear relevant facial muscles and a rise of stress hormones. Whereas placebo administration before CCK-4 revealed no significant panic and stress response, during placebo following CCK-4 stimulations a psychophysiological conditioning effect could be observed without rise in HPA-axis activity. Our findings indicate the possibility to measure different intensities of panic anxiety and conditioning effects with a facial EMG method. Dissociation of HPA-activity and fear relevant facial muscle activity is in accordance with former results about spontaneous panic attacks.